Formation Characteristics of PCDD/Fs in the Co-combustion and Pyrolysis Process of Coal and Sewage Sludge - Mumin Rao; Xiangbo Zou; Ji Ye; Yunfeng Ma; Tieying Mao; Xiaoqing Lin; Xiaodong Li; Jianhua Yan; Shiwei Qin; Cao Kuang (Aerosol and Air Quality Research)
Abstract Co-combustion technology of coal and sewage sludge (SS) was encouraged and recommended in China. Previous studies most focused on its influence on combustion characteristics, migration characteristics of heavy metals in fly ash, and emission of conventional pollutants, etc., but less reported the formation characteristics of polychlorinated-ρ-dibenzodioxins and dibenzofurans (PCDD/Fs). To well reveal it, this study carried out five parallel experiments, including the pyrolysis of SS, the combustion of SS, the co-combustion of coal and SS with the proportion of 0%, 2.5% and 5%, respectively. The emission concentration of PCDD/Fs respectively increased from 0.42 ng g−1 (0.0022 ng I-TEQ g−1) to 0.54 ng g−1 (0.0030 ng I-TEQ g−1) and 1.70 ng g−1 (0.0305 ng I-TEQ g−1) with increasing blending proportion of SS. The dominant part was also changed from PCDF (0.32 ng g−1 in M-0%, 0.38 ng g−1 in M-2.5%) to PCDD (1.11 ng g−1 in M-5%). The formation concentration of PCDD/Fs in the combustion process of SS was about 0.34 ng g−1 (0.0019 ng I-TEQ g−1). In the pyrolysis process of SS, the concentration of PCDD/Fs was 0.59 ng g−1 (0.0037 ng I-TEQ g−1). The de novo synthesis should be the major formation pathway of PCDD/Fs in the co-combustion process of coal and SS. On the basis of sufficient carbon sources, the PCA analysis revealed the chlorine source (Cl) and metal catalyst (Fe) should contribute a lot on the formation of PCDD/Fs. The results paved the way for further optimization on the operation of co-combustion of coal and SS and assist in controlling the PCDD/F emission from co-combustion process.